Reference values for balance in physically active elderly women Valores de referência para o equilíbrio em idosas fisicamente ativas Valores de referencia para el equilibrio en mujeres mayores físicamente activas - Hauser E. (2020)
© 2020, Redprint Editora Ltda. All rights reserved.Introduction: Body balance is one of the most important factors related to falls, quality of life, and in-dependence, and its evaluation is therefore important. Objective: To establish reference values for balance tests in physically active older women from different age groups. Methods: The sample consisted of 192 physically active women aged 60 to 79 years who were submitted to the following tests: timed up and go (TUG), one-leg stand (OLS), five-repetition chair stand (CS-5), functional reach (FR), and tandem stand test (TST). Descriptive statistics (percentile analysis) and the Mann-Whitney U test were used. Results: In older women aged 60 to 69 years, the values indicating “good” balance were a score less than 5.7 s in the TUG, achieving 30 s of OLS, performing the CS-5 test in less than 8.5 s, and a result greater than 35.5 cm in the FR test. In older women aged 70 to 79 years, the values indicating “good” balance were a score less than 5.9 s in the TUG, achieving 30 s of OLS, performing the CS-5 in less than 8.5 s, and a result greater than 33 cm in the FR test. In the TST, most of the physically active subjects achieved the ceiling performance. Conclusion: The reference values obtained are similar to or better than those reported in the literature. The use of the TST is not recommended for physically active older women because of its low discrimina-tory power in this group. Level of evidence III; Study of non consecutive patients; without consistently applied reference ‘‘gold’’ standard.